2020
DOI: 10.1007/s00484-020-01984-z
|View full text |Cite
|
Sign up to set email alerts
|

Weather suitability for outdoor tourism in three European regions in first decades of the twenty-first century

Abstract: Outdoor tourism and recreational activities strongly depend on actual meteorological conditions. Traditionally, in three studied regions, the peak of tourists' streams concentrates in summer months. In the present study, we assess suitability of weather conditions for various forms of outdoor tourism in different regions of Serbia, Poland and Ukraine. Additionally, how the location of the station differentiates temporal patterns of weather suitability will be discussed. To analyse the suitability of weather co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…3), thermoneutral ('no thermal stress') conditions were observed in the analysed locations only in the cool half of the year, on 7-11% of days in the year. This was in contrast to the conclusions of Błażejczyk et al (2020), who found weather in Poland from September to April to be very suitable for active recreation in an analysis applying the Weather Suitability Index (WSI). This metric includes components related to thermal sensation, but also elements of the weather (precipitation, snow cover), which determine the attractiveness of particular atmospheric conditions for tourists (Błażejczyk, 2007;Błażejczyk & Matzarakis, 2007;Błażejczyk & Kunert, 2011), and thus differs from the UTCI approach, which focusses on the thermal strain of the human organism.…”
Section: Discussioncontrasting
confidence: 91%
“…3), thermoneutral ('no thermal stress') conditions were observed in the analysed locations only in the cool half of the year, on 7-11% of days in the year. This was in contrast to the conclusions of Błażejczyk et al (2020), who found weather in Poland from September to April to be very suitable for active recreation in an analysis applying the Weather Suitability Index (WSI). This metric includes components related to thermal sensation, but also elements of the weather (precipitation, snow cover), which determine the attractiveness of particular atmospheric conditions for tourists (Błażejczyk, 2007;Błażejczyk & Matzarakis, 2007;Błażejczyk & Kunert, 2011), and thus differs from the UTCI approach, which focusses on the thermal strain of the human organism.…”
Section: Discussioncontrasting
confidence: 91%
“…with reduced risk of organism overheating involved by great metabolism. On the other hand cold stress at elevated locations, accelerated by strong winds, is unsuitable for passive recreation forms like sun and air bathing (Błażejczyk & Sitek, 2003;Miszuk et al, 2016;Błażejczyk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The authors have reported an influence of geographical location (longitude and latitude) on bioclimatic features of studied cities. Recently, Błażejczyk et al (2020) have compared the suitability of bioclimatic weather features for outdoor tourism in three European countries: Poland, Serbia and Ukraine. While general features of climate (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[18]. Therefore, the issue of OTC in urban areas has become the subject of the numerous studies over the past two decades [1,2,11,[19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The results of different bioclimatic and biometeorological studies have proven the great applicability of this method in the assessment of urban OTC. For instance, the UTCI has been applied for these purposes worldwide, e.g., Canada [23,33], Brazil [34,35], Australia [32], India [36], China [32,37,38], South Korea [33], Iran [39,40], Saudi Arabia [19], Russia [23], Greece [1,41], Czech Republic [42], Poland [17], France [43], other European regions [20,44,45], etc.…”
Section: Introductionmentioning
confidence: 99%